2009
DOI: 10.1016/j.jcrs.2009.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in higher-order aberrations: Spherical aberration in the South East Asian Chinese eye

Abstract: Corneal and ocular aberrations in South East Asian Chinese eyes were significantly greater than that reported in other populations. Population differences in wavefront errors were significant, and this should be noted in patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Significant differences in the refractive error range of the examined populations of Brunette et al and Zhang et al may explain the inconsistency in their results, with −3.50 to +3.50 D (across all included ages from six to 82 years) and −10.00 to +8.25 D, respectively, although Zhang et al reported no significant differences in HOAs between the myopes, emmetropes and hyperopes within each age group. Additionally, Caucasian and Asian adults, and Chinese and Malay children, have been reported to exhibit HOA profile differences, particularly for primary spherical aberration (Z40); therefore, ethnic variation may also exist between the HOA profiles of Canadian and Chinese children. Given the cross‐sectional designs of both studies, longitudinal studies are required to further the current understanding of the temporal variations in HOAs during childhood.…”
Section: Hoas and Agementioning
confidence: 99%
“…Significant differences in the refractive error range of the examined populations of Brunette et al and Zhang et al may explain the inconsistency in their results, with −3.50 to +3.50 D (across all included ages from six to 82 years) and −10.00 to +8.25 D, respectively, although Zhang et al reported no significant differences in HOAs between the myopes, emmetropes and hyperopes within each age group. Additionally, Caucasian and Asian adults, and Chinese and Malay children, have been reported to exhibit HOA profile differences, particularly for primary spherical aberration (Z40); therefore, ethnic variation may also exist between the HOA profiles of Canadian and Chinese children. Given the cross‐sectional designs of both studies, longitudinal studies are required to further the current understanding of the temporal variations in HOAs during childhood.…”
Section: Hoas and Agementioning
confidence: 99%
“…Using the large population study by Salmon and van de Pol as the reference norm for HOAs in a healthy population [5], we found the similarities in the distribution of predominant aberrations but distinct differences in the magnitude of aberrations. For the corneal RMS-HOA, the normal United States people were 0.479±0.124 µm (KL & HB 2009); the Malaysia (ethnic Chinese) people were 0.591±0.256 µm [18]. RMS-HOAs of anterior corneal surface in our research were 0.598±0.125 µm, more than that of Caucasian.…”
Section: The Ethnic Characteristics Of Our Data Of Corneal Hoasmentioning
confidence: 49%
“…To account for the reversed coma effect seen in our data (Figure 4D) we would need a Q value of approximately +0.55, as depicted by the open circles in Figure 5. With increasing anterior corneal asphericity, spherical aberration usually becomes more positive 42,43 . Therefore, we correlated the slope of horizontal coma with central spherical aberration.…”
Section: Resultsmentioning
confidence: 99%